A novel anchorage system for CFRP cable: Experimental and numerical investigation. (15th June 2018) - Wu, Jingyu; Xian, Guijun; Li, Hui
Abstract: In this paper, a novel bonding anchorage system characterized by the diverged arrangement of CFRP bars inside socket with resin-based adhesive was proposed for CFRP cable. The anchorage system was experimentally tested to verify its performance and numerical simulations were conducted to investigate the influential factors in proposed anchorage to cable bearing capacity and failure mode. In the anchorage system, the bonding capacity with the selected high-efficient adhesives and the bonding length in socket determined by the simulated bonding behaviors was verified experimentally. Besides, the effect of the adhesive stiffness on the uniformity of the tensile stress distribution of CFRP bars in cable, as well as the effects of the adhesive wedge action on the cable fracture mode were investigated with the finite element simulation. The experimental tests and numerical simulations reveal the influences of resin-based adhesive and adhesive wedge action on anchorage performance.